"In Essence I'm Only Reflecting": Teacher Strategies for Fostering Historical Reasoning in Whole-Class Discussions. Issue 1 (1st August 2011) - Van Drie, Jannet; Van Boxtel, Carla
Abstract : Dialogue is important for the development of students' thinking and reasoning in a domain. In history classrooms, however, teacher talk often dominates. This study examines strategies history teachers use to foster students' historical reasoning in whole-class discussions. Data consisted of three video-taped whole-class discussions of three different teachers, as well as stimulated recall-interviews with these teachers. Fine-grained analyses of the whole-class discussions, both qualitative and quantitative, shed light on the various strategies these teachers use to elicit students' historical reasoning. It was found that the teachers used various strategies, some of which are more general and some of which or more shaped by characteristics of the history domain. The teacher seems to have an important role in enriching students' historical reasoning by deepening the discussion by focussing on one specific component of historical reasoning, or by broadening the discussion by introducing different components. Which strategies are used seem to be related to choices made by the teachers with regard to the goals of the lesson, the task, and their knowledge of specific characteristics of the students as age, level, and abilities.